PENGARUH PRICE TO BOOK VALUE, EARNING PER SHARE, RETURN ON EQUITY, DAN DEBT TO EQUITY RATIO TERHADAP STOCK PRICE PADA PERUSAHAAN INDEKS LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dwi Fitria Ningsih; Raden Priyo Utomo; Ibnu Abni Lahaya (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
Dwi Fitria Ningsih, The Effect of Price to Book Value,  Earning Per Share, Return On Equity and Debt to Equity Ratio to Stock Price (Study Case:  LQ45 Index Companies Listed on Bursa Efek Indonesia Period 2013-2015), under the guidance of Mr. Raden Priyo Utomo and Mr. Ibnu Abni LahayaThere are several financial ratios that could describe the financial condition and performance of a company in fundamental analysis. These financial ratios could help companies to identify various weaknesses and strengths of a company and could predict profit from investment in the capital market.the effect of Price to Book Value,  Earning Per Share, Return On Equity and Debt to Equity Ratio to Stock Price in LQ45 Index companies for one year ahead.The methods of data collection in this study are using documentation method which is in the form of the company’s annual reports and literature study method that use literature books as references that relate to the problems in this study.The analytical tools in this study are descriptive analysis, multiple regression analysis, classical assumption test, and hypothesis test using computer program called SPSS version 22The results showed that between Price To Book Value (X1), Earning Per Share (X2), Return On Equity (X3), have positive and significant effect to Stock Price and Debt to Equity Ratio (X4) has a positive effect but not significant to Stock Price (Y) variable in Index LQ45 Companies that listed on Bursa Efek Indonesia (BEI) for one year ahead. The amount of influence is shown by the coefficient of determination of 0,714 or 71,4%. This number has the intention that the influence of variables X1, X2, X3, and X4 simultaneously affect the variable Y as much as 71.4%, while the remaining 28.6% is influenced by other factors.